The Existance of Larvae and Dengue Fever Incidence in Kedurus Sub-District in Surabaya - Shinta Anggraini (Universitas Airlangga, 2018)
Surabaya is an endemic area of Dengue Hemorrhagic Fever (DHF) because every year there is always DHF case incidence. In 2013, there were 2.207 DHF incidences, 816 incidences in 2014, 640 incidences in 2015, and 938 incidences in 2016. This research aimed to analyze the relationship between existences of mosquito larvae with the DHF incidence in Kedurus sub-district, Karang Pilang district, Surabaya. This was observational research with cross sectional design. Unit analysis of this research is the houses, and there were 100 respondents' house inspected in RW II which randomly selected. Data collected by observing mosquito larvae in water reservoir and recorded in observation sheet, while the data related to DHF incident obtained by interviewing respondents with questionnaires. Statistical analysis used in this research was chi-square test.Density figure in RW II, Kedurus sub-district, Surabaya area is categorized as average. Result showed that there is significant relationship between existence of mosquito larvae) with DHF incidents (p=0,000 in Kedurus sub-district. It is suggested that the community of RW II, Kedurus sub-district to do prevention activity and vector control to reduce the risk of DHF incidence. They also have to be more frequent to clean the water reservoir for daily use whether it's inside or outside the house.